(untitled) (Sahayaatra सहयात्रा, 2026)
This article focuses on the relationship of the Sanskrit language with the languages of the world, its influence on global language, literature, religion, philosophy, and grammar, as well as its relevance in the present time. In the article prepared on the basis of a qualitative approach, primary sources include the Sanskrit language and various texts related to it, while secondary sources comprise world languages and materials related to them. In order to study the relationship between Sanskrit and other languages, as well as its influence on literature, religion, philosophy, and grammar, materials have been collected from various dictionaries. For analytical purposes, historical linguistics—particularly theories of Glottochronology, the tree model, and linguistic reconstruction—has been used as the foundational framework. The key conclusion drawn from this analysis is that among the many languages that evolved after the origin of life on Earth, Sanskrit stands as one of the most ancient. However, just as changes have occurred over time in the world, languages—being an integral part of existence—have also undergone changes. Therefore, the language that was in use at the beginning of human civilization was not the same as today’s Sanskrit but a closely related predecessor. Sanskrit is the language in which the Vedas, Upanishads, epics, Puranas, Dharmashastra (religious texts), literature, Economics (Arthashastra), Ayurveda, Architecture (Vastu Shastra), Yoga, Astrology, and the world’s most structured grammar— Aṣṭādhyāyī —have been composed. Owing to the immense knowledge preserved in these texts, Sanskrit has had a profound and lasting influence not only on the literature, philosophy, religion, and grammar of the Indian subcontinent but also on those of other countries like Germany, the United Kingdom, the United States, China, and Japan. Sanskrit has even made significant contributions to the field of modern linguistics. With its beautiful, harmonious, and logical structure, Sanskrit is a language capable of preserving a vast store of knowledge and science, making it highly valuable in today’s global context.